FABRICATION OF PLASTIC SCINTILLATOR USING POLYSTYRENE MATRIX BASED - Nuri, Hafni Lissa; Pancoko, Marliyadi; Jami, Abdul; Subhiyah, Hana; Ardiyati, Tanti; Sari, Dian Maya; Desviana, Adinda Tisha (Spektra: Jurnal Fisika dan Aplikasinya, 2022)
Experiments on making a plastic scintillator with polystyrene as a base material mixed with fluorescent compounds (primary and secondary dopants) have been performed. Primary dopants (PTP) used to produce emission at wavelengths of visible light and secondary dopants (POPOP) to shift the visible wavelengths to wavelengths that could be detected by Photomultiplier Tube (PMT) ) were carried out. Experiments were performed on the melting points condition of these materials, which had previously been subjected to a thermo-mechanical analysis using a Thermogravimetric Analysis-Differential Scanning Calorimetry (TGA-DSC) machine, where the melting point was in the range of 200-240°C. Furthermore, the fabrication was carried out using the extrusion technique, where polystyrene pellets mixed with PTP (1.5% by weight) and POPOP (0.05% by weight) were fed into an extrusion machine which has four hot areas to obtain a thin plate plastic scintillator. The plates were then analyzed with a UV-Vis Spectrophotometer to determine the absorption spectrum and Fluorescence Spectrophotometer to determine the emission spectrum. From the results of the analysis, it was found that the samples that went through scintillation pellets and without the addition of antioxidants had absorption spectrum data of 330 nm and emission spectrum of 421 nm. These values are in accordance with the characteristics of plastic scintillators on the market.